Effects of Microplastics Exposure on the Acropora sp. Antioxidant, Immunization and Energy Metabolism Enzyme Activities - Xiao, Baohua; Li, Dongdong; Liao, Baolin; Zheng, Huina; Yang, Xiaodong; Xie, Yongqi; Xie, Ziqiang; Li, Chengyong (Frontiers in Microbiology, 2021)
Microplastic pollution in marine has increased rapidly in recent years and it can bring negatively influence on marine organism health. Scleractinian coral is the one of important species in the coral ecosystems that is sensitive to microplastic greatly. However, whether microplastic causes the corals physiological disruption such as oxidative stress, immunity, and energy metabolism is unclear. In the present study, the physiological responses of the coral Acropora sp. are determined after exposure to polyethylene terephthalate (PET), polyamide 66 (PA66), and polyethylene (PE) microplastic for 96 hours. The results showed that there were about 4-22 items/nubbin on the surface of coral skeleton and 2-10 items/nubbin on the inside of skeleton in the MPs exposure groups. The density of endosymbiont was decreased (1.12×105 - 1.24×105 cell/cm2) in MPs exposure groups compared with control group. Meanwhile, the chlorophyll content was reduced (0.11 - 0.76 µg/cm2) after MPs exposure. Further analysis revealed that antioxidant enzymes in corals tissues were up-regulated (Total antioxidant capacity T-AOC 2.35×10-3-1.05×10-2 mmol/mg prot, Total superoxide dismutase T-SOD 3.71-28.67 U/mg prot, glutathione GSH 10.21 - 10.51 U/mg prot). The alkaline phosphatase (AKP) was inhibited (1.44 - 4.29 U/mg prot), while nitric oxide (NO) was increased (0.69 - 2.26 µmol/g prot) for cell signal. Moreover, lactate dehydrogenase (LDH) was down-regulated in the whole experiment period (0.19 - 0.22 U/mg prot), and Glucose-6-phosphate dehydrogenase (G6PDH) for cell the phosphate pentoses pathway was also reduced (0.01 - 0.04 U/mg port). It showed that the endosymbiont was released and chlorophyll was decreased. In addition, a disruption could occur under MPs exposure, which was related to anti-oxidant, immune and energy metabolism.